2019
DOI: 10.1111/dom.13847
|View full text |Cite
|
Sign up to set email alerts
|

GLP‐1 receptor agonists for prevention of cardiorenal outcomes in type 2 diabetes: An updated meta‐analysis including the REWIND and PIONEER 6 trials

Abstract: A meta‐analysis of cardiovascular outcome trials (CVOTs) comparing glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) and placebo concerning cardiorenal outcomes in patients with type 2 diabetes (T2D) is presented. An electronic search without language restrictions up to June 15, 2019 was conducted to determine eligible trials. A meta‐analysis of available trial data was undertaken, using a random‐effects model to calculate overall hazard ratios (HRs) and 95% confidence intervals (CIs). Data from seven CVOTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 25 publications
9
83
0
5
Order By: Relevance
“…Our results are consistent overall with a post hoc analysis of pooled SUSTAIN and PIONEER data, which also showed that the effect of semaglutide vs comparators on MACE was largely consistent across different CV subgroups [35]. Furthermore, a meta-analysis including CVOTs for all GLP-1 receptor agonists found no significant heterogeneity in the effect of these therapies in subgroups with a history of CVD vs those with no history of CVD [36]. Although there were no significant subgroup interactions in the meta-analysis, there was a numerically lower risk of MACE in subjects with a history of CVD (−14%, hazard ratio 0.86) vs those without such a history (−6%, hazard ratio 0.94) [36].…”
Section: Findings In Context Of the Broader Literaturesupporting
confidence: 89%
“…Our results are consistent overall with a post hoc analysis of pooled SUSTAIN and PIONEER data, which also showed that the effect of semaglutide vs comparators on MACE was largely consistent across different CV subgroups [35]. Furthermore, a meta-analysis including CVOTs for all GLP-1 receptor agonists found no significant heterogeneity in the effect of these therapies in subgroups with a history of CVD vs those with no history of CVD [36]. Although there were no significant subgroup interactions in the meta-analysis, there was a numerically lower risk of MACE in subjects with a history of CVD (−14%, hazard ratio 0.86) vs those without such a history (−6%, hazard ratio 0.94) [36].…”
Section: Findings In Context Of the Broader Literaturesupporting
confidence: 89%
“…Some meta-analyses (5,13,14) suggest the presence of heterogeneity in estimates for MACE and CV death with GLP-1 receptor agonists, although this is mostly due to the results of a single trial with lixisenatide. Likewise, there is some heterogeneity in the estimate for CV death with SGLT2 inhibitors.…”
Section: Changes To Consensus Recommendationsmentioning
confidence: 99%
“…While a chance effect may not be excluded saxagliptin should be avoided in such patients. Two recent meta-analyses including data from 7 CVOTs showed that GLP-1 RAs afford a 9% relative risk reduction of hHF as compared to placebo [19,20]. This effect is much greater with SGLT-2is which have shown a relative risk reduction of 31% over a similar median duration of follow-up [5] (Table 1).…”
Section: Effects Of the New Glucose Lowering Drugs On Heart Failure Ementioning
confidence: 99%